ANALYSIS OF COMPLICATIONS IN PATIENTS UNDERGOING TRANSFORAMINAL LUMBAR INTERBODY FUSION: A CRITICAL EXAMINATION OF SURGICAL INTERVENTIONS FOR LUMBAR CANAL STENOSIS - SINGH, RAHUL KUMAR; DEEPAK, PRIYANK; TOPGIA, CHHEWANG (International Journal of Current Pharmaceutical Research, 2024)
Objective: The lumbar spine undergoes degenerative changes with age, leading to lumbar canal stenosis (LCS). Surgical interventions, including transforaminal lumbar interbody fusion (TLIF), become essential when conservative measures fail. Understanding complications associated with TLIF is crucial for informed decision-making and improved patient outcomes. Methods: A study involving 40 LCS patients undergoing TLIF was conducted at Indira Gandhi Medical College, Shimla. Records were retrospectively evaluated for 15 patients (pre-May 2016) and prospectively for 25 patients (May 2016-May 2017). Surgical indications, inclusion/exclusion criteria, preoperative preparation, and TLIF procedures were outlined. Postoperative care and follow-up assessments were detailed. Statistical analysis utilized SPSS 17.0 with a significance level of 0.05. Results: Age and sex distribution demonstrated a significant association (p=0.0049), with a male predominance (57.5%). Occupation analysis revealed 32.5% farmers, 15% laborers, 5% drivers, and 47.5% 'others.' Neurological deficits were present in 75% of cases, while facet joint arthropathy affected 67.5% of patients. Preoperative Oswestry Disability Index indicated severe disability in 62.5% of cases. Conclusion: This study provides critical insights into TLIF complications for LCS, emphasizing male predominance, occupation-related considerations, and significant preoperative disability. Findings contribute to refining surgical protocols, minimizing risks, and optimizing patient safety in TLIF for LCS, essential for advancing spinal surgery standards.